2012
DOI: 10.1029/2011ja017161
|View full text |Cite
|
Sign up to set email alerts
|

Statistical investigation of horizontal propagation of gravity waves in the ionosphere over Europe and South Africa

Abstract: [1] A statistical investigation into the horizontal propagation of $8-30 min gravity waves (GWs) in the ionosphere over a 1 year period from June 2010 to May 2011 is presented. The GWs were observed by multipoint continuous Doppler sounding systems installed in the Czech Republic and in the Western Cape, South Africa. Measurements of GW propagation in the ionosphere over South Africa have never been presented before. Simultaneous measurements from nearby ionosondes made it possible to estimate the height of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Similar seasonal behavior, i.e., poleward propagation in summer and equatorward in winter, was observed in previous studies using HF Doppler sounding over the Czech Republic, South Africa, and Argentina (Chum et al 2010(Chum et al , 2012(Chum et al , 2014. Ding et al (2011) investigated MSTIDs over Central China using GPS-TEC measurements.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Similar seasonal behavior, i.e., poleward propagation in summer and equatorward in winter, was observed in previous studies using HF Doppler sounding over the Czech Republic, South Africa, and Argentina (Chum et al 2010(Chum et al , 2012(Chum et al , 2014. Ding et al (2011) investigated MSTIDs over Central China using GPS-TEC measurements.…”
Section: Resultsmentioning
confidence: 64%
“…1. A more detailed description of similar Doppler sounding systems operating in other locations can be found in Chum et al (2010Chum et al ( , 2012, and Doppler sounding theory is described in more detail in Chum et al (2016).…”
Section: Doppler Sounding Systemmentioning
confidence: 99%
“…Tsugawa et al (2007) found from GPS measurements over the USA on 28 November 2006 daytime: λ x = 300-1000 km. Chum et al (2012) found using multiple Doppler sounders in the Czech Republic values of λ x between 100 and 300 km.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…Also the wave observed by Tsugawa et al (2007) over the USA on 28 November 2006 in the daytime with λ x similar to this paper, propagated southeastward. Chum et al (2012) found that the TIDs over the Czech Republic in the winter propagated with azimuths between 90 and 180 • .…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation